(untitled) (Global Business Management Review (GBMR), 2022)
Innovation and creativity are the two essential elements of a country in moving towards developed country and high-income people by 2020 especially in Malaysia. High-income people are the people who innovate. Malaysia has implemented a transformation in all fields so that it is aligned with the execution of the country’s economic transformation to produce innovation-based economy, including the agricultural sector. Agriculture is critical field to ensure national food security. Thus, System of Rice Intensification (SRI) is an innovative methodology found can enhance the production and productivity of agricultural at optimal level. Many studies show this method has been successful in increasing productivity of rice in various countries such as Vietnam, Indonesia, and India. In Malaysia, SRI began practice in 2009. However, there are various methods of yield productivity measurement of SRI rice has been used in the area. Therefore, this exploratory case study will identify and discuss methods of SRI paddy yield productivity measurement that has been used in Agro Belantik Corporation in Sik, Kedah. In addition, methods Muda Agricultural Development Authority (MADA) will also be discussed. The methodology used is an interview with SRI practitioners and observation. The scope of this study is rice farmers use SRI methods in Sik, Kedah. Results showed that there are some differences and similarities in the calculation method used in productivity measurement of rice yields produced using the SRI method.